Differential Genome Size and Repetitive DNA Evolution in Diploid Species of Melampodium sect. Melampodium (Asteraceae) - McCann, Jamie; Macas, Jiří; Novák, Petr; Stuessy, Tod F.; Villaseñor, Jose L.; Weiss-Schneeweiss, Hanna (Frontiers in Plant Science, 2020)
Plant genomes vary greatly in composition and size mainly due to the diversity of repetitive DNAs and the inherent propensity for their amplification and removal from the host genome. Most studies addressing repeatome dynamics focus on model organisms, whereas few provide comprehensive investigations across the genomes of related taxa. Herein, we analyze the evolution of repeats of the 13 species in Melampodium sect. Melampodium, representing all but two of its diploid taxa, in a phylogenetic context. The investigated genomes range in size from 0.49 to 2.27 pg/1C (ca. 4.5-fold variation), despite having the same base chromosome number (x = 10) and very strong phylogenetic affinities. Phylogenetic analysis performed in BEAST and ancestral genome size reconstruction revealed mixed patterns of genome size increases and decreases across the group. High-throughput genome skimming and the RepeatExplorer pipeline were utilized to determine the repeat families responsible for the differences in observed genome sizes. Patterns of repeat evolution were found to be highly correlated with phylogenetic position, namely taxonomic series circumscription. Major differences found were in the abundances of the SIRE (Ty1-copia), Athila (Ty3-gypsy) and CACTA (DNA transposon) lineages. Additionally, several satellite DNA families were found to be highly group-specific, although their overall contribution to genome size variation was relatively small. Evolutionary changes in repetitive DNA composition and genome size were complex, with independent patterns of genome up and downsizing throughout the evolution of the analyzed diploids. A model-based analysis of genome size and repetitive DNA composition revealed evidence for strong phylogenetic signal and differential evolutionary rates of major lineages of repeats in the diploid genomes.